Factors affecting utilization and satisfaction of maternal health care services among mothers of neonates in Paropakar maternity and women’s hospital - Neupane, Shristi; Thapa, Janak; Mahotra, Narayan Bahadur; Bhandari, Lok Raj (International Journal Of Community Medicine And Public Health, 2021)
Background: Knowledge and use of maternal health service is an effectual way to reduce the risk of maternal morbidity and mortality which can be influenced by multiple factors. Maternal service utilization thus plays an important role during pregnancy, childbirth, and the postpartum period. The aim of the study was to analyse antenatal services as proxy indicator for study purpose. Methods: A descriptive cross-sectional study was conducted in post-natal ward of Paropakar maternity and women’s hospital after ethical approval from the Ethical Review Board of the Nepal Health Research Council and Institutional Review Committee of Paropakar maternity and women’s hospital and 210 samples were collected by a simple random sampling method. Statistical analysis was done using SPSS 16.0. Results: Out of 210 participants, only 100 (47.6%) had antenatal care as per protocol. The median age of the women delivering in hospital was 25 years. Women having household income more than 10,000 (OR=2.125, 95% CI=1.065-4.241, p=0.032), impact of mass media for utilization of antenatal care service (OR=14.261, 95% CI=4.881-41.670, p value<0.001), and women’s taking an hour or less to reach health facility (OR=2.763, 95% CI=1.293-5.903, p value=0.009) were found to be statistically significant. Conclusions: Majority of women in the study didn’t utilized full antenatal care service as per protocol. There is a need for different community based maternal and child health programs targeting the reproductive aged women and adolescent groups.